PENGARUH ALOKASI DANA DESA TERHADAP JUMLAH PENDUDUK MISKIN DI KABUPATEN LEBAK - Usep Siswadi; Tian Septiantini; Firmansyah Firmansyah (Sekolah Tinggi Ilmu Ekonomi La Tansa Mashiro, 2021)
Poverty always attracts the attention of various groups, both academics and practitioners. Various theories, concepts and approaches are constantly being developed to uncover the curtain of the